Constraints on new physics with light mediators and generalized neutrino interactions via coherent elastic neutrino nucleus scattering - Karadag, S.; Deniz, M.; Karmakar, S.; Singh, M. K.; Demirci, M.; Li, H. B.; Lin, S. T.; Mustamin, M. F.; Sharma, V.; Singh, L.; Singh, V.; Wong, H. T. (AMER PHYSICAL SOC, 2025)
We investigate new physics effects on coherent elastic neutrino nucleus scattering within the framework of nonstandard interactions and generalized neutrino interactions. Additionally, we examine the possibility of light mediators from a simplified model that includes all possible Lorentz-invariant interactions of vector, axialvector, scalar, pseudoscalar, and tensor types. Constraints and allowed regions at the 90% CL for masses and couplings in each new physics scenario have been obtained through the analysis of TEXONO data, which includes two datasets from a high-purity n-type point contact germanium detector in 2016 and an advanced p-type point contact Ge detector in 2025. The results are presented in comparison with other reactor and accelerator-based neutrino experiments for complementarity.
Keywords: SIMPLIFIED MODELS; PROGRAM; Astronomy & Astrophysics; Physics